2016
DOI: 10.1007/s00170-016-8436-4
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty analysis of deep drawing using surrogate model based probabilistic method

Abstract: Deep drawing is an important manufacturing process in industry. In order to obtain high-quality products produced by deep drawing, the set of design variables used in forming operation is designed through deterministic optimization. However, in real forming process, the design variables show variability and randomness which will affect the product quality. These uncertainties are an inherent characteristic of nature and cannot be avoided. This paper focuses on uncertainty analysis of deep drawing with the cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(11 citation statements)
references
References 25 publications
(22 reference statements)
0
11
0
Order By: Relevance
“…Senn and Link [28,29] as well as Breitsprecher et al [41] used neural networks for surrogate modelling in deep drawing whereas Morand et al [42] and Huang et al [43] used kriging models for this task. Our research [44] related to modelling of draw-in as well as drawing aid force signals showed highest modelling accuracy by using linear regression approaches which is in accordance with the results in [23, see Table 4], especially compared to neural networks for regression.…”
Section: Modelling Of Sensor Signalsmentioning
confidence: 99%
“…Senn and Link [28,29] as well as Breitsprecher et al [41] used neural networks for surrogate modelling in deep drawing whereas Morand et al [42] and Huang et al [43] used kriging models for this task. Our research [44] related to modelling of draw-in as well as drawing aid force signals showed highest modelling accuracy by using linear regression approaches which is in accordance with the results in [23, see Table 4], especially compared to neural networks for regression.…”
Section: Modelling Of Sensor Signalsmentioning
confidence: 99%
“…[46]). Therefore, much of the recent work has focused on statistical descriptions of variability within FEM, for assessing the sensitivity of defect predictions to the scatter of the parameters under analysis [19,35,47]. In FEM, the material properties are commonly described using physicsbased constitutive models.…”
Section: Sheet Metal Formingmentioning
confidence: 99%
“…Two input features related to process parameters were also considered: the friction coefficient and the blank holder force (BHF). The mean value of the friction coefficient is 0.144 for all materials, with r/l ¼ 20% [19]. For the BHF, two mean values were considered, which correspond to a lower and an upper level of the process window.…”
Section: Simulated Data Setsmentioning
confidence: 99%
“…For these reasons, the stochastic modelling and uncertainties quantification of sheet metal forming processes are of current industrial interest. In recent years, several researchers have modelled the influence of the uncertainty sources on the final product variability, by resorting to Monte Carlo method [3,4], design of experiences techniques [5,6] and metamodels [7,8].…”
Section: Intr Introduction Oductionmentioning
confidence: 99%